1986
DOI: 10.1159/000260964
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology and Acid/Anion Profiles of Enamel Surface Plaque from an in situ Caries Appliance

Abstract: The microbiological species and acid/anion profiles of the plaque-like material which accumulates on exposed surfaces of enamel sections mounted in the experimental troughs of the previously described in situ caries appliance were studied. Each experiment lasted 1 week and the volunteers’ diet and oral hygiene patterns were unaltered, except that interproximal plaque was allowed to accumulate in an interproximal space adjacent to one of the troughs. The appliance was removed once per day to facilitate cleansin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
2

Year Published

1991
1991
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 5 publications
1
9
0
2
Order By: Relevance
“…This was confirmed experimentally, with the relative proportions of the four main groups of micro organisms being almost identical for section and ac rylic plaques, while both were significantly different from natural tooth plaque with respect to gram-posi tive cocci and bacilli. Creanor et al [1986a], comparing 1-week plaque is olated from natural tooth surfaces and enamel sec tions, also found higher proportions of gram-positive cocci in enamel section plaque, while the microflora obtained from smooth tooth surface plaque was simi lar to the results of the present study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This was confirmed experimentally, with the relative proportions of the four main groups of micro organisms being almost identical for section and ac rylic plaques, while both were significantly different from natural tooth plaque with respect to gram-posi tive cocci and bacilli. Creanor et al [1986a], comparing 1-week plaque is olated from natural tooth surfaces and enamel sec tions, also found higher proportions of gram-positive cocci in enamel section plaque, while the microflora obtained from smooth tooth surface plaque was simi lar to the results of the present study.…”
Section: Discussionsupporting
confidence: 81%
“…These include testing the cariogenic potential of sugars and foods [Brudevold et al, 1988], investigating the remineralizing potential of fluoridecontaining mouthrinses and dentifrices [Featherstone et al, 1982], and studying the microbiology of early colonization of human enamel and root surfaces [Ny vad and Kalian, 1987] and occlusal fissures [Theilade et al, 1974], However, while tooth-derived surfaces should re semble the in vivo situation more closely than artifi cial materials, the accessibility of saliva to these appli ance-borne tooth components, the proximity of the sampling sites to the appliance material, and the method by which plaque is allowed to accumulate on their surface may all affect the microfiora which sub sequently forms. The only previous study comparing microbial composition and acid anion profiles of plaque derived from natural tooth surfaces with plaque overlying enamel sections mounted on an ap pliance was carried out by Creanor et al [1986a] and involved 1 subject.…”
mentioning
confidence: 99%
“…Microbiological and biochemical studies have shown that the plaque formed initially [Creanor et al, 1986a] on the enamel sections, and present subsequently [Macpherson et al, 1990], is similar to natural plaque.…”
Section: Discussionmentioning
confidence: 94%
“…3,[5][6][7][8][9] Hence, it is clearly of much importance for experimental analysts to obtain a complete determination of the short-chain organic acid profile of active carious lesions in order to allow a full evaluation of the demineralization properties of carious dentin. The organic acid contents of dental plaque and carious dentin have been previously monitored by labour-intensive, relatively time-consuming laboratory methods such as those involving gasliquid chromatography (GLC), 10,11 column chromatography, 5,6 HPLC, 12 isotacaphoresis 7,13 or high pressure ionic exchange chromatography. 14 In the case of the latter technique, for example, plaque samples were ultrasonicated, filtered through a membrane and bubbled with helium prior to their eventual injection onto the chromatographic apparatus.…”
Section: Introductionmentioning
confidence: 99%